Heart rate variability and psychological correlete as overload indicators in the Spanish field hockey national team - Cervantes, J.; Florit, D.; Parrado, E.; Rodas, G.; Capdevila, L. (Archivos de medicina del deporte, 2008)
Several studies assessing heart rate variability (HRV) during training and competitive season have shown that long and short-term exercise training cause shift from vagal tone to sympathetic activation of autonomic nervous system. To our knowledge, no study to date has investigated the association between HRV and psychological factors and their responses to over load state of elite athletes. In these sense, to diagnose overreaching and to avoid overtraining it is necessary to know both physical and psychological symptoms in athletes. During a preparatory period for Beijing Olympic Games, time and frequency domain heart rate variability with Omega Wave System device and precompetitive anxiety, mood state and subjective fatigue with CSAI_2, POMS and fatigue psychological questionnaires were determinates on the hockey Spanish national team (age 25,76 ± 3,40). Data were collected in a room at ambient temperature (22° C to 24° C) between 7:00 AM and 8:30 AM, in two separate sessions: (1) 70 days before of the Olympic games after a short recovery period (2) 40 days before to the Olympic games, one day after a strenuous training. Results showed negative correlation between somatic anxiety and RMSSD (r = -,536; p = 0,026), pNN50 (r = -,598; p = 0,011) and HFms² (r = -,653; p = 0,004); between fatigue perception and RMSSD (r = -,634; p = 0,006), HFms² (r = -,625; p = 0,007). Changes from the first to the second session showed that pNN50 (Wilkoxon test; p = 0,026) and RMSSD (p = 0,017) and SDNN (p = 0,017) decreased after a strenuous training while fatigue perception increased (p = 0,024). In conclusion, these data suggest that there is a negative association between HRV parasympathetic indexes and fatigue perception and somatic anxiety. Low vagal-related indexes of HRV and the increasement of fatigue perception due to over load state of athletes, can be useful to adjust the intensity of training.